Frequência de anomalias cromossômicas e análise de variações genômicas estruturais em indivíduos atendidos em um laboratório de citogenética em Cuiabá – MT - Venâncio, Amanda Cristina (2018)
Changes in chromosomes are the cause of several disorders in humans and currently represent, together with congenital anomalies of other origins, the second cause of infant mortality in Brazil. Aneuploidy, a change in the total number of chromosomes, is the most frequent type of chromosomal abnormality and is easily identified by karyotype examination. Some structural chromosome rearrangements may require more detailed analysis by advanced molecular cytogenetics techniques for accurate diagnosis and prognosis. The aim of this study was to analyze the results of peripheral blood karyotypes performed in a cytogenetic laboratory in Cuiabá-MT over a period of 28 years (1988 to 2016), as well as to perform a better investigation by the cytogenetic technique of comparative genomic hybridization based on microarray (array-CGH), in selected cases of structural chromosomal rearrangements. 4,375 karyotype results were studied, with chromosomal abnormalities being identified in 14%. Of these, aneuploidies were the most frequent type of anomaly, including trisomies of chromosomes 21, 18 and 13, and monosomy X. Down's syndrome was observed in more than half of the total cases (56.8%), and Turner's syndrome represented the second most common chromosomal disorder (16%). Of the structural changes the deletions were more frequently found. Cytogenetic investigation was performed in 3 cases: ring 20 chromosome; duplication 10q and duplication 1q. The characterization of the annular chromosome by the CGH array revealed the presence of two genomic imbalances in the long arm of the chromosome: a microduplication (302,774Kb) and a microdeletion (1.4 Mb). Twenty genes involved in the rearrangement were identified, and a genotypephenotype correlation could be proposed for the case. The NTSR1 gene has also been identified as a possible candidate gene for clinical dysfunctions presented by long arm deletion ring 20 carriers.